2009
DOI: 10.1097/naq.0b013e3181a10c86
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organizational Change on Work-related Empowerment, Employee Satisfaction, and Motivation

Abstract: This article reports the results of a longitudinal quantitative study on nurses' views on factors promoting and impeding empowerment and examines the relationship between work-related empowerment and background variables in one hospital. Data were collected using a self-administered questionnaire and analyzed statistically. Nurses gave lowest assessments of promoting factors on the second measurement occasion, a time when the organization was going through major changes. Both job satisfaction and motivation sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 25 publications
5
43
0
Order By: Relevance
“…Staff with positive perceptions of barriers to change will also have high levels of job satisfaction [1]. The two groups were staff with positive perceptions of job satisfaction and staff with negative perceptions of job satisfaction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Staff with positive perceptions of barriers to change will also have high levels of job satisfaction [1]. The two groups were staff with positive perceptions of job satisfaction and staff with negative perceptions of job satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…While there is common acknowledgement of the frequency of these changes, there has been little research that addresses how staff working in these services anticipate and respond to innovation [1,2], and none that focuses specifically on acute in-patient wards in the mental health services. An exploration of these issues in the mental health services is important because distinct social processes and contextual features exist here [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous research has shown (de Jonge et al, 2001;Yu, Gu, Zhou, & Wang, 2008 This refers to the evaluation of whether a job provides opportunities for the development of personal abilities and knowledge and if workers can relate their work role to their values or end results other than simply utilitarian ones (to have one's time occupied and to obtain a reward for work completed). Between these two variables (which we deal with as if they were only one), the ability for personal development probably has the most weight (Kuokkanen, Suominen, Harkonen, Kukkurainen, & Doran, 2009;de Jong et al, 2001;Chen & Chen, 2008), but the meaning of work has also found support in the literature (Ritter & Anker, 2002). …”
Section: Please Insert Figure 1 Herementioning
confidence: 99%
“…This is because universities are the most important elements of the teaching-learning process in society today (10,11). Therefore, organizational learning is the main way to make knowledge work and improve organizational efficiency, particularly in the education system.…”
mentioning
confidence: 99%